An Improved Distributed Multi-User Cooperative Spectrum Sensing Method Based on DCS - Jianwu Zhang; Xiaoyan Chen; Xiaorong Xu (Dianxin kexue)
Distributed compressed sensing theory extends the application of compressed sensing theory, which brings single signal compression sampling to signal group compression sampling. Cooperative spectrum sensing technology uses space set macros to compensate detection error problems during the process of single-user wideband spectrum sensing. However, it increases computational complexity in the process of signal reconstruction. Aiming to this problem, an improved distributed multi-user cooperative spectrum sensing method based on DCS was proposed. On the basis of original OMP algorithm, the improved method reduced reconstruction algorithm's computational complexity through the utilization of previous spectrum occupancy situation. Simulation results indicate that, the proposed method achieves the same effect with the original algorithm under the circumstances of slow spectrum occupancy changes. Meanwhile, in the case of more cognitive users, this method reduces the reconstruction complexity significantly.